2017
DOI: 10.1111/jgh.13788
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of liver stiffness in patients with hepatitis C virus infection who received direct‐acting antiviral therapy and achieved sustained virological response

Abstract: These results suggest that early improvement of liver stiffness starts during the administration of DAAs in patients who achieve SVR, and this effect is particularly pronounced in patients with progressive liver fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

16
73
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 99 publications
(91 citation statements)
references
References 29 publications
(50 reference statements)
16
73
2
Order By: Relevance
“…For LS evaluation, the transient elastography method was used in the studies described above and, according our knowledge, there are insufficient trials in which the SWE method was used in patients with antiviral treatment. In the Tada et al study, the results of 210 patients treated with daclatasvir and asunaprevir were analyzed, and it was found that the average LS decreased by 1.4 kPa between baseline and EOT and 2.6 kPa between baseline and FU24, which is consistent with our results [40]. It should be noted that the type of DAA regimen used made no difference.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…For LS evaluation, the transient elastography method was used in the studies described above and, according our knowledge, there are insufficient trials in which the SWE method was used in patients with antiviral treatment. In the Tada et al study, the results of 210 patients treated with daclatasvir and asunaprevir were analyzed, and it was found that the average LS decreased by 1.4 kPa between baseline and EOT and 2.6 kPa between baseline and FU24, which is consistent with our results [40]. It should be noted that the type of DAA regimen used made no difference.…”
Section: Discussionsupporting
confidence: 81%
“…In the Miyaki et al study, they found that in patients who achieved SVR, a reduction in the AFP level, ALT activity, and platelet count were observed [46]. In a larger group of patients, in a more detailed analysis, this observation was confirmed by Tada et al [40]. In our group of patients, we found improvement in albumin and ALT levels.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…However, LS measurements may also be affected by factors other than fibrosis stage, for example, inflammatory activity,28, 29 and intrahepatic pressure. There are a few studies demonstrating a decrease in LS in patients on eradication of HCV where both pre‐ and post‐treatment ARFI elastography assessments were available 30. It is probable that such reduction in ARFI elastography values indicates not only the improvement in fibrosis but also inflammation in the liver because of treatment.…”
Section: Discussionmentioning
confidence: 99%